Students’ Errors in Solving Integer Multiplication and Division Word Problems - Sheila Ananda; Nurhayadi Nurhayadi; Akhyar H. M. Tawil; I Nyoman Murdiana (Indonesian Technology and Education Journal, 2026)
This study aims to describe the types of errors and the factors causing such errors made by Grade VII students at SMPN 19 Palu in solving word problems involving multiplication and division of integers. Mathematics education plays a vital role in developing students’ reasoning abilities; however, many students still encounter difficulties in operations with integers, particularly in solving contextual problems. Although Newman’s Error Analysis has been widely applied, research that thoroughly examines the errors of junior high school students in word problems on integer multiplication and division remains limited, especially in the context of Indonesian students using the Newman’s Error Analysis framework. This research employs a qualitative descriptive approach, involving two Grade VII students as research subjects. Data were collected through written tests and interviews, then analyzed using the Miles and Huberman model with reference to the procedures of Newman’s Error Analysis: reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The findings identified four types of errors: comprehension, transformation, process skill, and encoding errors, while no reading errors were found. Comprehension errors occurred because students failed to identify all relevant information presented in the problems, while transformation errors stemmed from an inability to convert verbal information into mathematical models. Process skill errors resulted from careless calculations, which in turn led to errors in writing the final answers. No reading errors were found among any of the subjects. This study enhances understanding of the characteristics of student errors in the context of word problems on integer operations at the junior high school level. The findings highlight the importance of instruction that emphasizes understanding word problems, constructing mathematical models, and developing the habit of rechecking calculations, so that errors at every stage of problem solving can be minimized.